Houses full of owls: Oracular owls in Isaiah - Sherman, Phillip Michael (Journal for the study of the Old Testament, 2026)
The image of the owl in the Bible is very much like actual owls: elusive, silent, and usually obscured from easy sight. Their presence is rarely noted in commentary literature. Even the very terms which modern scholars believe refer to owls are subject to debate and uncertainty. Owls (allegedly) appear in three contexts in the Bible: the food regulations in the Torah (Leviticus 11 and Deuteronomy 14), once in Psalms (Psalm 102:7), and in prophetic oracles against the nations (Isaiah 13 and 34; Zephaniah 2). After considering these passages, we will explore what can be known regarding the ?cultural symbolism? of owls in the context of the biblical world and highlight which emotions and associations owls might have evoked in the ancient world. Finally, we will consider the long history of human-owl interactions and explore insights from fields associated with Critical Animal Studies in order to provide a deeper understanding of biblical texts.